Microbial biosurfactants: Green alternatives and sustainable solution for augmenting pesticide remediation and management of organic waste - Shiv Shankar Markam; Aman Raj; Ashwani Kumar; Mohammed Latif Khan (Current Research in Microbial Sciences)
Pesticide pollution remains a significant environmental challenge, necessitating the exploration of sustainable alternatives. Biosurfactants are a class of unconventional surface-active chemicals that are produced by microorganisms. Biosurfactants have many applications in treating oil spills, emulsifiers, pharmaceuticals, and agriculture. Compared to chemical surfactants, they have benefits such as biodegradability, less toxicity, and a greener option because they are derived from microbes. Biosurfactants have recently been shown to have the potential to speed up pesticide cleanup. Biosurfactants are used in pesticide remediation because of their exceptional foaming ability, high selectivity, and wide range of pH, salinity, and temperature operating windows. Microbial biosurfactants emerged as potential agents for the treatment of organic waste and agricultural residue. This review unfolds the promising realm of microbial biosurfactants as green solutions for environmental sustainability, particularly in agricultural practices, with special reference to pesticide remediation. This article highlights the escalating need for eco-friendly alternatives, paving the way for discussing biosurfactants. Moreover, the articles discuss in detail various advancements in the field of rapid screening of biosurfactants, either using a conventional approach or via advanced instruments such as GC-MS, HPLC, NMR, FTIR, etc. Furthermore, the article unveils the molecular mechanisms and the microbial genes driving biosurfactant synthesis, offering insights into enhancing production efficiency. Moreover, the article explores diverse applications of microbial biosurfactants in sustainable agriculture, ranging from soil remediation to crop protection. The article also highlights the various functions of microbial biosurfactants for enhancing the decomposition and recycling of organic waste and agricultural residues, emphasizing their potential for sustainable waste management strategies. Overall, the review underscores the pivotal role of microbial biosurfactants as green alternatives for addressing pesticide pollution and advancing environmental sustainability.